Optimal parking design by parallelogram concept in Bingle parking lot at McDonald’s Seremban 2 / Najir Tokachil … [et al.] - Tokachil, Najir; Ahmad Ettihad, Nur Farahana; M. Noor Hashim, Rabiatul Fatanah; Md Hazi, Nursyafifazzry (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Nowadays, the lack of sufficient parking spaces can cause congestion, especially in an urban area because the number of cars has rapidly increased. Therefore, this study was done on how to overcome this problem by optimising the number of parking lots. Using the parallelogram concept that Bingle proposed, the parking lot of McDonald’s Seremban 2 was selected as a scope for our study. There were three factors involved in this concept which were the length, width, and angle of the parking lot. The angle of the parking lot was assigned as a main factor that influences the number of parking lots which are 30°,45°, 60° and 90°. As a result, the most appropriate angles for the parking lot in McDonald’s Seremban 2 are 60° and 90°, which can contribute to a greater number of parking lots compared to other parking degrees. The AutoCAD software was used to illustrate the parking lot of McDonald’s Seremban 2 based on the angles obtained from this result. In the future, other factors such as length, width, or access lane of any width of a parking lot need to be emphasized to obtain an accurate result.